Smartphone Digital Image Using for Determination of DCH by a Diazotization Reaction - Abbas, Ruba F.; Waheb, Ali A.; Hami, Howraa K.; Mahdi, Neda I. (Current Analytical Chemistry, 2020)
Background: Simple, sensitive, and economic colorimetric device based on a smartphone digital image coupled with Color Grab™ application was developed for DCH drug determination. The method is based on the diazotization reaction of benzocaine with DCH drug to get an orange azo dye. Methods: Variable parameters such as volumes of reagents, the internal walls and ambient light have been analyzed and optimized. From the optimized conditions, a calibration curve was created by the effective intensity (IG) of an orange azo dye, a correlation of determination is 0.999 and limit of detection 0.808 mg/L. Results: The results of the Smartphone method were statistically compared with the reference method using a t-test and found to be a good agreement. Conclusion: This method requires neither solvent extraction and temperature control, also it has achieved an extensive linear range and low limit of detection compared with different methods reported in the literature.
Keywords: DCH